2018
DOI: 10.1101/415372
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The sensation of groove is affected by the interaction of rhythmic and harmonic complexity

Abstract: 48Groove is defined as the pleasurable desire to move to music. Research has shown that 49 rhythmic complexity modulates the sensation of groove but how other musical features, such as 50 harmony, influence groove is less clear. To address this, we asked people with a range of musical 51 experience to rate stimuli that varied in both rhythmic and harmonic complexity. Rhythm 52 showed an inverted U-shaped relationship with ratings of pleasure and wanting to move, whereas 53 medium and low complexity chords were… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 59 publications
(7 reference statements)
4
28
2
Order By: Relevance
“…When compared to high levels of syncopation, low and moderate syncopation levels in both movement synchrony conditions resulted in higher interpersonal closeness. This finding might relate to the inverted U-shaped relationship between syncopation, pleasure, and body movement: rhythms with moderate levels of syncopation are more enjoyed and induce more movement than rhythms with low and high levels of syncopation 41,42 . This inverted U-shape can also explain why differences in interpersonal closeness between synchronous and asynchronous movements were higher for videos with moderate syncopation levels compared to high syncopation levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to high levels of syncopation, low and moderate syncopation levels in both movement synchrony conditions resulted in higher interpersonal closeness. This finding might relate to the inverted U-shaped relationship between syncopation, pleasure, and body movement: rhythms with moderate levels of syncopation are more enjoyed and induce more movement than rhythms with low and high levels of syncopation 41,42 . This inverted U-shape can also explain why differences in interpersonal closeness between synchronous and asynchronous movements were higher for videos with moderate syncopation levels compared to high syncopation levels.…”
Section: Discussionmentioning
confidence: 99%
“…This inverted U-shape can also explain why differences in interpersonal closeness between synchronous and asynchronous movements were higher for videos with moderate syncopation levels compared to high syncopation levels. Matthews and colleagues 41 showed that stimuli with moderate syncopation levels are enjoyed most and high syncopation levels least. Assuming that the current auditory stimuli, which were selected from Matthews and colleagues, evoked the same pattern of enjoyment, our finding confirms the synchrony × enjoyment of the music interactions found in Studies 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…The significant fixed effects of the Pysh and Neelix tracks in all sway directions (see Table 6), renders additional evidence to the links between high-event, high-groove music with entrainment and spontaneous body movement (Madison et al, 2011;Janata et al, 2012;Gonzalez Sanchez et al, 2018;Matthews et al, 2019). The effect of stimuli with lower onset density were less predominant (Rhythm, Metronome, Bratten), with no statistical significance in the AP direction.…”
Section: Effect Of Music On Head Swaymentioning
confidence: 96%
“…To tackle this issue, the concepts of wants, desires, appetence, groove and the action impulse (i.e., action readiness) were all plotted on a field distinguishing them by ostensible differences in valence (negative or positive tension) and their specificity to movement (see Figure 1). The concept of groove, for instance, is specific to a felt need to move, and is ostensibly conceived as a positive force or tension (17). It is highly contextual to the influence of music, however.…”
Section: Defining Categorizing and Describing Desires/urges To Move mentioning
confidence: 99%
“…The concept of "appetence" (i.e., strong and provoking desires for movement) has shed light on mechanisms of addiction (16). In musicology, the concept of "groove" describes the ability of music to generate feelings of urge to move (17). There appears to be considerable overlap in the concepts of desires, wants, urges and related constructs, yet they seem to vary by the dimensions of magnitude, specificity to movement behavior, whether the desire is conscious and felt, as well as valence.…”
Section: Introductionmentioning
confidence: 99%